Good boys [videorecording (DVD)] - Stupnitsky, Gene; Tremblay, Jacob; Williams, Keith L., 2007-; Noon, Brady; Forte, Will; Gordon, Molly, 1994- (Universal Pictures Home Entertainment, 2019)
After being invited to his first kissing party, twelve-year-old Max is panicking because he doesn't know how to kiss. Eager for some pointers, Max and his best friends Thor and Lucas decide to use Max's dad's drone to spy on a teenage couple making out next door. But when things go ridiculously wrong, the drone is destroyed. Desperate to replace it before Max's dad gets home, the boys skip school and set off on an odyssey of epically bad decisions.